Development of fibre optic bio-/chemical sensors for healthcare applications - Liu, LiangLiang (2019)
Sensing by using optical fibres is a promising approach for application in the healthcare field due to their small dimension, the capability of working in a harsh environment (i.e. high electromagnetic interference (EMI), corrosive environment) and potential for remote sensing. The possibility to measure clinically significant biomarkers would allow the diseases to be tracked in real time and supports diagnostic activities at clinical point-of-care (POC). This PhD thesis aims to demonstrate the versatility of the fibre optic sensor (FOS) for sensing of multiple clinical parameters including antibodies, gases (CO2, relative humidity (RH) and NH3) and drugs (fentanyl). Four types of FOSs are fabricated and included in the thesis, which are (I) a long-period fibre grating (LPG) based IgM sensor, (II) a Fabry–Pérot interferometer CO2 sensor for the simultaneous measurement of gaseous CO2 and RH, (III) a reflection sensor for simultaneous measurement of gaseous CO2 and NH3, (IV) an LPG sensor for detecting carboxyl-fentanyl from liquid solution. Each sensor is prepared by combining an optical fibre sensing platform with the developed sensing materials for measuring of one or more of the mentioned parameters. Developed sensors were characterised in laboratory conditions for evaluating the critical parameters of the sensor, i.e. sensitivity, specificity and response time. The developed IgM sensor is fabricated by depositing composite nanoparticles with a silica core and gold shell structure to create a porous structure and large surface area for IgM interaction to the receptors anchored on the shell. The sensor demonstrates the capability of detecting IgM in a wide concentration range from 15.6 μg/mL to 1000 μg/mL with limit of detection (LOD) of 0.015 ng/mm2 and a minimum detected concentration of 15.6 μg/mL. It shows a high specificity to IgM with a negligible response to the interfering protein, i.e. Bovine serum albumin (BSA). The sensor with such detection range and LOD can potentially be applied for the diagnostics of IgM related diseases such as selective IgM deficiency (SIgMD) and neonatal infection. The ability to monitor the binding process kinetically supports the application of the sensor in POC diagnostics. A Fabry–Pérot interferometer (FPI) hybrid sensor is prepared by combination of the FPI with a colourimetric measurement for measuring RH and CO2. A sensing film comprised of silica matrix doped with thymol blue and tetramethylammonium hydroxide (TMAH) is dip coated on the tip of an optical fibre forming a cavity for the FPI sensor. The sensor responds to the concentration of CO2 range from 0-6 % and RH level from 0 to 90 % with negligible cross-talk between the two parameters. The sensitivity for both parameters is 18 % of reflection value change per 5 % of CO2 and 0.14 nm per 1 % of RH. It is immune to the temperature in the tested range from 25 ℃ to 40 ℃. Due to the slow response time, 98s for CO2 and 32s for RH, the sensor is applicable to measure the CO2 and RH in an application where the response time is not critical such as transcutaneous CO2 (TcCO2) measurement. The developed sensor was successfully implemented to measure breath gases from a healthy human volunteer with a percent error of 3.1 % and 2.2 % for CO2 and RH respectively when taking the commercial datalogger (33 BLG, CO2 Meter, USA) as the golden standard. The percent error is the difference between the measurement from developed sensor and the reference sensor, divided by the value of reference sensor and multiplied by 100 %. The sensing of gaseous NH3 in this thesis is achieved by using the sensitive dye Tetrakis-(-4-sulfophenyl) porphine (TSPP) that changes its colour after the interaction with NH3. The FOS for the simultaneous measurement of NH3 and CO2 is fabricated by incorporating two sensitive dyes, TSPP and thymol blue into one fibre detection system. Two dyes are separately doped into a sol-gel matrix and an ethyl cellulose (EC) plastic film and coated on the two ends of a 2x2 optical fibre coupler. The two dyes have different spectral properties with distinctive absorption wavelengths across the detection range that facilitates detection of the target gases. The sensor exhibits a sensitivity of ~15 % of increase in intensity for responding ~5 % of CO2 and sensitivity of -0.003 /ppm for gaseous NH3. It shows no cross-talk between NH3 and CO2 measurement and demonstrates the ability to measure both gases simultaneously. The LOD for NH3 is 3.9 ppm which is lower than the required concentration for breath analysis in diagnosis of diseases such as renal disease or stomach ulcers; therefore the sensor is not ready yet for breath analysis. An LPG functionalised with molecularly imprinted polymer (MIP) nanoparticles is reported for the detection of carboxyl-fentanyl. A reference LPG was inscribed into a same optical fibre for compensating the temperature effect during the measurement. The sensor is tested in a concentration range from 0 ng/mL to 1000 ng/mL and shows a minimum detected concentration of 50 ng/mL. The wavelength shift is 4.95± 0.3 nm at a concentration of 1000 ng/mL after compensating the temperature effect. From the research described in this thesis, the versatility of the FOS platform in measuring clinical biomarkers for the diagnostic purpose with the ability to measure multiple parameters simultaneously is demonstrated. FOS can be applied to meet unmet clinical needs. For example, measuring the relevant biomarker in a particularly clinical condition such as MRI scanning room in which conventional electronic sensors interfere with the electromagnetic field. FOS is a low-cost sensor and can be made as a portable sensor for home and emergency use. The FOS is believed having great impacts in the future healthcare field as it offers a competitive sensor in diagnosis and monitoring, especially in the home use and wearable sensors market due to its miniaturised size, excellent biocompatibility and immunity to electromagnetic interference (EMI). It also provides a new opportunity to study phenomenon or conduct research which has not been studied yet due to the limitations of conventional sensors (i.e. bulky size, non-compatible to biological samples and effect of EMI).